1992
DOI: 10.1016/s0006-3495(92)81713-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the chirality of the glycerol backbone on the bilayer and nonbilayer phase transitions in the diastereomers of di-dodecyl-beta-D-glucopyranosyl glycerol

Abstract: We have studied the physical properties of aqueous dispersions of 1,2-sn- and 2,3-sn-didodecyl-beta-D-glucopyranosyl glycerols, as well as their diastereomeric mixture, using differential scanning calorimetry and low angle x-ray diffraction. Upon heating, both the chiral lipids and the diastereomeric mixture exhibit characteristically energetic L beta/L alpha phase transitions at 31.7-32.8 degrees C and two or three weakly energetic thermal events between 49 degrees C and 89 degrees C. In the diastereomeric mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

1994
1994
2000
2000

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 64 publications
(124 reference statements)
3
18
0
Order By: Relevance
“…Other approaches to the study of the effects of lipid interfacial structure on lipid phase behavior have involved comparisons of glycerolipids with ester-linked hydrocarbon chains with appropriate amido-linked counterparts (Curatolo et al, 1982(Curatolo et al, , 1985Chowdhry et al, 1984b), comparisons of normal glycerolipids with analogs containing "conformationally restricted backbones" (Blume and Eibl, 1981;Singer et al, 1983), and comparisons of glycerolipids with 1,3-linked hydrocarbon chains with comparable 1,2-linked analogs (Eibl and Blume, 1979;Serralach et al, 1983;Stumpel et al, 1981;Chowdhry et al, 1984a;Dluhy et al, 1985). It has also been demonstrated that the propensity of some glycerolipids to form inverted nonlamellar phases can be altered by the chirality of the glycerol backbone (Mannock et al, 1992(Mannock et al, , 1994) and by the location of modestly sized hydrophobic groups near the glycerol backbone of the lipid (Lewis et al, 1994a). Such studies clearly show that lipid phase behavior and organization can be significantly altered by chemical changes in this portion of the lipid molecule.…”
Section: Introductionmentioning
confidence: 99%
“…Other approaches to the study of the effects of lipid interfacial structure on lipid phase behavior have involved comparisons of glycerolipids with ester-linked hydrocarbon chains with appropriate amido-linked counterparts (Curatolo et al, 1982(Curatolo et al, , 1985Chowdhry et al, 1984b), comparisons of normal glycerolipids with analogs containing "conformationally restricted backbones" (Blume and Eibl, 1981;Singer et al, 1983), and comparisons of glycerolipids with 1,3-linked hydrocarbon chains with comparable 1,2-linked analogs (Eibl and Blume, 1979;Serralach et al, 1983;Stumpel et al, 1981;Chowdhry et al, 1984a;Dluhy et al, 1985). It has also been demonstrated that the propensity of some glycerolipids to form inverted nonlamellar phases can be altered by the chirality of the glycerol backbone (Mannock et al, 1992(Mannock et al, , 1994) and by the location of modestly sized hydrophobic groups near the glycerol backbone of the lipid (Lewis et al, 1994a). Such studies clearly show that lipid phase behavior and organization can be significantly altered by chemical changes in this portion of the lipid molecule.…”
Section: Introductionmentioning
confidence: 99%
“…as well as the temperature range over which they are stable, was found to depend on the chirality of the glycerol backbone (Mannock et al, 1992). The absence of stable QlI phases in the lipids studied here2 may be due to a critical difference in the balance of headgroup-hydrocarbon chain contributions to the stability of the fluid phases of the dialkyl 13-GalDAGs with chain lengths of 12 and 14 carbon atoms.…”
Section: Mesophase Transitionsmentioning
confidence: 65%
“…The f3-Ga1DAGs used in this study were synthesized according to literature methods (Ogawa and Beppu, 1982;van Boeckel et al, 1985;Glew et al, 1991;Mannock et al, 1987Mannock et al, , 1992 using dialkylglycerols prepared from the 1,2-sn or racemic isopropylidene glycerols (Aldrich Chemical Co., Milwaukee, WI) or 2,3-isopropylidene-sn-glycerol (Pfanstiehl Laboratories, Waukegan, IL). The caand (3-anomers of the 1-GalDAGs were separated as their peracetates by chromatography on a silica gel column (Davisil, 200-425 mesh) which was eluted with a gradient of hexane and ethyl acetate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These temperatures correspond to the two eutectic mixtures of enantiomeric and racemic crystals, and the shape of the (pseudo) binary phase diagram indicates that the crystal of the racemate is a racemic compound, as in the case of the bulk compound. Chiral discrimination has been found in a number of DSC studies of phospholipid bilayers [120][121][122][123][124][125][126]. 14) when equimolar solutions of the R and S isomers were mixed.…”
Section: Mixed Vesicles and Liposomesmentioning
confidence: 98%